Masked Priming of Conceptual Features Reveals Differential Brain Activation during Unconscious Access to Conceptual Action and Sound Information - Trumpp, Natalie M. (Public Library of Science, 2013)
Previous neuroimaging studies suggested an involvement of sensory-motor brain systems during conceptual processing in support of grounded cognition theories of conceptual memory. However, in these studies with visible stimuli, contributions of strategic imagery or semantic elaboration processes to observed sensory-motor activity cannot be entirely excluded. In the present study, we therefore investigated the electrophysiological correlates of unconscious feature-specific priming of action- and sound-related concepts within a novel feature-priming paradigm to specifically probe automatic processing of conceptual features without the contribution of possibly confounding factors such as orthographic similarity or response congruency. Participants were presented with a masked subliminal prime word and a subsequent visible target word. In the feature-priming conditions primes as well as targets belonged to the same conceptual feature dimension (action or sound, e.g., typewriter or radio) whereas in the two non-priming conditions, either the primes or the targets consisted of matched control words with low feature relevance (e.g., butterfly or candle). Event-related potential analyses revealed unconscious feature-specific priming effects at fronto-central electrodes within 100 to 180 ms after target stimulus onset that differed with regard to topography and underlying neural generators. In congruency with previous findings under visible stimulation conditions, these differential subliminal ERP feature-priming effects demonstrate an unconscious automatic access to action versus sound features of concepts. The present results therefore support grounded cognition theory suggesting that activity in sensory and motor areas during conceptual processing can also occur unconsciously and is not mandatorily accompanied by a vivid conscious experience of the conceptual content such as in imagery.